2009
DOI: 10.1016/j.ijnonlinmec.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of a stress wave through a virtual functionally graded foam

Abstract: Stress wave propagation through a Functionally Graded Foam Material (FGFM) is analysed in this paper using the Finite Element Method. A Finite Element model of the Split Hopkinson Pressure Bar (SHPB) is developed to apply realistic boundary conditions to a uniform density foam and is validated against laboratory SHPB tests. Wave propagation through virtual FGFMs with various gradient functions are then considered. The amplitude of the stress wave is found to be shaped by the gradient functions, i.e. the stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 34 publications
1
30
0
1
Order By: Relevance
“…Ali et al (2008) established a graded energy absorbing structure-a inspiration from the geometry in a banana peel, and gave the theoretical prediction of the behavior under low velocity based on the equations derived by Gibson and Ashby (1997). Kiernan et al (2009) had found the superiority of graded cellular materials on impact resistance and energy absorption for creating impact resistant structures and cushioning materials. Compared with a uniform foam with equal mass, Cui et al (2009) suggested that a functionally graded foam can exhibit superior energy absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al (2008) established a graded energy absorbing structure-a inspiration from the geometry in a banana peel, and gave the theoretical prediction of the behavior under low velocity based on the equations derived by Gibson and Ashby (1997). Kiernan et al (2009) had found the superiority of graded cellular materials on impact resistance and energy absorption for creating impact resistant structures and cushioning materials. Compared with a uniform foam with equal mass, Cui et al (2009) suggested that a functionally graded foam can exhibit superior energy absorption.…”
Section: Introductionmentioning
confidence: 99%
“…This would build upon the work already carried out by Cui et al, [2] and Kiernan et al, [3]. While the methodology outlined in this paper appears to achieve global results quite similar to those of the HEX model while using only one independent input parameter, it is unlikely to be a successful method when studying the local deformation of a foam on a cellular scale.…”
Section: Discussionmentioning
confidence: 69%
“…Its dimensions are 0.5m 3 . The four nodes of the bottom face are constrained in the vertical direction while a velocity boundary condition of -0.425 m·s −1 is applied to nodes of the top face, giving a simulation time of 1 second.…”
Section: Displacement Controlled Compressionmentioning
confidence: 99%
“…The principle of stress wave testing is based on differences in the velocity of stress waves propagating in different materials, since the velocity of sound in healthy wood is much higher than in voids or in decaying wood (Halabe et al 1997;Wang et al 2004;Feng and Li 2008). Several studies of this technology have been performed, both experimentally and with simulations (Kiernan 2009). These studies have indicated that stress wave testing can effectively diagnose the defects in the wood (Liang 2008).…”
Section: Fig 1 Example Of An Ancient Chinese Timber Frame Buildingmentioning
confidence: 99%